Morbidity of Left Pancreatectomy when Associated with Multivisceral Resection for Abdominal Mesenchymal Neoplasms - Berselli, Mattia; Coppola, Sara; Colombo, Chiara; Pennacchioli, Elisabetta; Fiore, Marco; Gronchi, Alessandro (JOP. Journal of the Pancreas, 2011)
Context Resection of adjacent visceral organs is often required in surgery for abdominal mesenchymal tumors. Objectives To analyze the specific perioperative morbidity and mortality of a left pancreatectomy in multivisceral resections for mesenchymal tumors. Patients This paper considered all patients treated at National Cancer Institute, Milan, Italy, from January 1997 to May 2009 for the resection of abdominal mesenchymal neoplasms requiring a concomitant left pancreatectomy. The extension of surgery, pathology of both the tumor and the pancreatic tissue, completeness of resection, administration of pre or postoperative treatments and postoperative outcome were analyzed. The overall survival of the entire population was also assessed. Results Fifty-seven patients affected by localized left retroperitoneal mesenchymal neoplasms or intra-abdominal gastrointestinal stromal tumors were identified. A macroscopically complete resection was achieved in all but 3 patients (5.3%) and the neoplastic involvement of pancreatic tissue was documented at pathology in 26 (45.6%) patients. Surgical postoperative complications occurred in 20 patients (35.1%); 7 patients (12.3%) developed a postoperative pancreatic fistula. With a median follow-up of the surviving patients of 32 months (interquartile range: 20-57 months), the overall survival at 5 years was 67.0%. Conclusion Left pancreatic resection seemed to be a safe procedure, even when it is part of a multivisceral resection for abdominal mesenchymal neoplasms. When margins are crucial for cure, the left pancreas should then always be resected, independently of its direct infiltration. Image: Kaplan-Meier estimates of overall survival for the entire series.